Shunting for idiopathic normal-pressure hydrocephalus: can we predict response?. (March 2011) - Batra, Sachin; Blitz, Ari; Moghekar, Abhay; Solomon, David; Rigamonti, Daniele
Patient selection based upon preshunt corroborative evaluation with tap test, lumbar drainage or measurement of outflow resistance provides long-term improvement in idiopathic normal-pressure hydrocephalus patients. The key is to select patients with the idiopathic normal-pressure hydrocephalus triad of symptoms, as well as ventriculomegaly for shunting, in order to improve the negative predictive value of our tests so that appropriate patients can be reliably excluded as being shunt refractory.